2019
DOI: 10.1080/2162402x.2019.1671761
|View full text |Cite
|
Sign up to set email alerts
|

In vivo generated human CAR T cells eradicate tumor cells

Abstract: Chimeric antigen receptor (CAR) T cells are in prime focus of current research in cancer immunotherapy. Facilitating CAR T cell generation is among the top goals. We have recently demonstrated direct in vivo generation of human CD19-CAR T cells by targeting CD8+ cells using lentiviral vectors (LVs). The anti-tumor potency of in vivo generated CAR T cells was assessed in human PBMC-transplanted NSG mice carrying i.v. injected CD19+ Nalm-6 tumor cells. A single injection of CD8-targeted LV delivering CD19-CAR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Signs of CRS, the presence of tissue‐invading CAR-T cells and the complete elimination of the B‐lymphocyte‐rich zones in spleens were detected ( 98 ). More recently, efficient eradication of tumors in transplanted mice was demonstrated upon a single vector injection ( 99 ). Although further investigations are desirable, these promising results have demonstrated that the in vivo engineering of human CD8 + CAR-T cells could substantially simplify their manufacturing and the development of future cell-based immunotherapies.…”
Section: Optimizing the Delivery In Vivo Of Car-t mentioning
confidence: 99%
“…Signs of CRS, the presence of tissue‐invading CAR-T cells and the complete elimination of the B‐lymphocyte‐rich zones in spleens were detected ( 98 ). More recently, efficient eradication of tumors in transplanted mice was demonstrated upon a single vector injection ( 99 ). Although further investigations are desirable, these promising results have demonstrated that the in vivo engineering of human CD8 + CAR-T cells could substantially simplify their manufacturing and the development of future cell-based immunotherapies.…”
Section: Optimizing the Delivery In Vivo Of Car-t mentioning
confidence: 99%
“…The ankyrin domains have been selected from libraries to guaranty their high affinity. ScFvs and DARPins have been introduced successfully in MV [67] and in Nipah virus envelope glycoproteins [61,68,69] to target oncolytic domains and hematopoietic cells in vitro and in vivo [48,68,[70][71][72].…”
Section: Envelope Glycoproteins Retargeted To Specific Hematopoietic mentioning
confidence: 99%
“…More recently, this team evaluated the same CD8NiV-LV delivering the anti-CD19 CAR in an NSG mice engrafted with CD19 + Nalm-6 tumor cells, followed by injection with human PBMCs [ 164 ]. A single injection of this CD8 targeted LV was sufficient to eliminate CD19 + Nalm-6 tumor cells, whereas in control animals tumor cells expanded in a uncontrolled manner [ 164 ]. Surprisingly, they detected also anti-CD19 CAR expression at the surface of NKT cells in vivo, since these cells also express the CD8α chain, the target of the CD8NiV-LV particles.…”
Section: In Vivo Car T Cell Generation Using Lentiviral Vectors Tamentioning
confidence: 99%